Deoxyribonucleic Acid Base Sequence Homologies of Some Budding and Prosthecate Bacteria - Moore, Richard L. (1972)
The genetic relatedness of a number of budding and prosthecate bacteria was determined by deoxyribonucleic acid (DNA) homology experiments of the direct binding type. Strains of Hyphomicrobium sp. isolated from aquatic habitats were found to have relatedness values ranging from 9 to 70% with strain “EA-617,” a subculture of the Hyphomicrobium isolated by Mevius from river water. Strains obtained from soil enrichments had lower values with EA-617, ranging from 3 to 5%. Very little or no homology was detected between the amino acid-utilizing strain Hyphomicrobium neptunium and other Hyphomicrobium strains, although significant homology was observed with the two Hyphomonas strains examined. No homology could be detected between prosthecate bacteria of the genera Rhodomicrobium, Prosthecomicrobium, Ancalomicrobium, or Caulobacter, and Hyphomicrobium strain EA-617 or H. neptunium LE-670. The grouping of Hyphomicrobium strains by their relatedness values agrees well with a grouping according to the base composition of their DNA species. It is concluded that bacteria possessing cellular extensions represent a widely diverse group of organisms.